Factors influencing self-management in patients with epilepsy: a systematic review and meta-analysis - Wenhao Tian; Xiaoxiao Yin; Wanya Pan; Chang Liu; Yuan Zhao; Leiwen Tang; Xiuqin Feng (BMC Nursing)
Abstract Background Self-management is significant for the quality of life, physical and mental health, and prognosis of patients with epilepsy. There is evidence that various factors significantly affect the level of self-management in people with epilepsy, however, the reported factors affecting self-management vary greatly. Therefore, it is particularly important to further unify and clarify the factors affecting self-management in people with epilepsy. Aims This study aimed to identify the influencing factors of epilepsy self-management, and provide help for researchers to develop more accurate intervention strategies and interventions. Design A systematic review and meta-analysis. Data sources From online databases, including PubMed, Web of Science, CINAHL, Embase, Cochrane Library, China National Knowledge Infrastructure, China Science and Technology Journal Database and Wan Fang Data. Review methods Two independent systematic searches of English and Chinese databases were conducted by two graduate students with evidence-based training. The searches combined MeSH terms and free terms and covered the period from the establishment of the databases to October 31, 2024. References were managed using EndNote 20. Then, two reviewers independently screened literature, assessed study eligibility using the Agency for Healthcare Research and Quality (AHRQ) and extracted data. After conducting a quality assessment of the included literature, meta-analysis was performed by using the obtained data. The degree of heterogeneity was also indicated by using I2 statistic. Results In 10 cross-sectional studies were selected from 2720 studies, Education, Gender, Income level, Employment, Marital status, Age, Duration of disease, Self-efficacy may be key factors affecting self-management in patients with epilepsy. Meanwhile, the meta-analysis result of Education(0.53, 95% confidence interval (CI):0.25 ~ 0.58), Gender(0.35, 95%CI:0.18 ~ 0.51), Income level(0.41, 95%CI:0.18 ~ 0.51), Employment(-0.49, 95%CI: -0.63 ~ 0.36), Marital status(-0.28, 95%CI: -0.43 ~ 0.13), Age(0.12, 95%CI:0.01 ~ 0.23), Duration of disease(0.47, 95%CI:0.11 ~ 0.83), Self-efficacy(0.28, 95%CI:0.21 ~ 0.35) were statistically significant (P<0.05) and result of Frequency of seizure(0.3, 95%CI:-0.63 ~ 1.22) was not significant(P>0.05). Conclusion The status of self-management in patients with epilepsy in some regions is still not optimistic. In this review, self-management in patients with epilepsy is affected by many factors, including education, age, self-efficacy, employment, marital status, duration of disease, gender, income level. These factors may provide more targeted interventions and education to improve the self-management and quality of life of epilepsy patients. Registration www.crd.york.ac.uk CRD42024619449, registered 10/12/2024.